Dendritic Cell-Based Immunotherapy in Advanced Sarcoma and Neuroblastoma Pediatric Patients: Anti-cancer Treatment Preceding Monocyte Harvest Impairs the Immunostimulatory and Antigen-Presenting Behavior of DCs and Manufacturing Process Outcome - Hlavackova, Eva; Pilatova, Katerina; Cerna, Dasa; Selingerova, Iveta; Mudry, Peter; Mazanek, Pavel; Fedorova, Lenka; Merhautova, Jana; Jureckova, Lucie; Semerad, Lukas; Pacasova, Rita; Flajsarova, Lucie; et al. (Frontiers in Oncology, 2019)
Despite efforts to develop novel treatment strategies, refractory and relapsing sarcoma and high-risk neuroblastoma continue to have poor prognoses and limited overall survival. Monocyte-derived dendritic cell (DC)-based anti-cancer immunotherapy represents a promising treatment modality in these neoplasias. A DC-based anti-cancer vaccine was evaluated for safety in an academic phase I/II clinical trial for children, adolescent and young adults with progressive, recurrent or primarily metastatic high-risk tumors, mainly sarcomas and neuroblastomas. The DC vaccine was loaded with self-tumor antigens obtained from patient tumor tissue. DC vaccine quality was assessed as DC yield, viability, immunophenotype, production of IL-12 and IL-10 and stimulation of allogeneic donor T-cells and autologous T-cells in allo-MLR and auto-MLR, respectively. Here we show that the outcome of the manufacturing of DC-based vaccine is highly variable in terms of both DC yield and DC immunostimulatory properties. In 30 % of cases, manufacturing resulted in a product that failed medicinal product specifications and therefore was not released for administration to a patient. Focusing on isolation of monocytes and the pharmacotherapy preceding monocyte harvest, we show that isolation of monocytes by elutriation is not superior to adherence on plastic in terms of neither DC yield nor viability or immunostimulatory capacity. Monocyte-interfering pharmacotherapy of trial patients prior to monocyte harvest was associated with impaired DC-based immunotherapy product outcome. Certain combinations of anti-cancer treatment resulted in a similar pattern of inadequate DC parameters, namely, a combination of temozolomide with irinotecan was associated with poor maturation and decreased immunostimulatory features of DCs and the combination of pazopanib, topotecan and MTD-based cyclophosphamide was associated with poor differentiation and decreased immunostimulatory parameters of DCs. Searching for a surrogate marker predicting adverse outcome of DC manufacturing in peripheral blood complete blood count prior to monocyte harvest, we observed an association between increased number of immature granulocytes in peripheral blood and decreased potency of DC-based product quantified by allo-MLR. We conclude that DC manufacturing yield and immunostimulatory quality of anti-cancer DC-based vaccines generated from patients’ monocytes was not influenced by monocyte isolation modality but was detrimentally affected by specific combinations of anti-cancer agents used prior to monocyte harvest.